THU0583 Effect of an online educational intervention in the knowledge of patient registries and patient-reported outcomes among rheumatologists. (15th June 2017) - Jackson, E; McCardell, E; Curtis, JR
Abstract : Background: Patient-reported outcomes (PROs) have evolved into an essential element in managing rheumatoid arthritis (RA), working in concert with physician-based tools to assess disease activity and health-related quality of life [1]. Objectives: A study was conducted to determine whether an online educational intervention could effectively address a knowledge gap and an underlying educational need in applying data from patient registries including PROs in the management of patients with RA. Methods: An online educational intervention focusing on advances in RA patient registries was developed and made available online. The intervention consisted of a 30-minute video-based roundtable discussion between 3 experts in treatment of RA. The intended audience was rheumatologists who treat patients with RA. The educational impact was assessed by comparing participants' responses to 4 identical paired pre- and post-assessment questions. Data representing a statistical sampling of the overall learner population was collected from 5/29/2015 through 8/13/2015. Statistical analysis comprised a paired (within-physician) 2-tailed t-test comparing mean pre-intervention and post-intervention scores, McNemar's χ2 statistic for measuring changes in responses to individual. Cramer's V determined the overall effect of the intervention. Results: Analysis of pre- versus post-activity responses by rheumatologists (n=36) demonstrated a significant improvement ( P <0.05) in overall knowledge with a robust effect size ( V =0.339). This activity resulted in increased knowledge surrounding several specific areas of RA management, such as drug safety, alternative means of collecting PRO data, and issues surrounding pregnancy in women with RA. The absolute percentage increases in correct individual responses to these topics (all P <0.05 except where noted), included: 33% increase (36% vs. 69%) in rheumatologists who recognized the results from pooled registries in Europe – 11 registries from 9 countries – regarding the safety of tumor necrosis factor-alpha inhibitor therapy, 28% increase (36% vs 64%) in rheumatologists who recognized that biosensor-based devices can provide passive data regarding patient outcomes, 14% increase (47% vs 61%, P =.237) in rheumatologists who identified the connected CORRONA-OTIS registries that provide information on patients with RA who become pregnant, 62% increase (19% vs 81%) in rheumatologists who identified that patient registry data can be used to support a risk mitigation strategy for prescribing a specific DMARD in patients who may become pregnant during therapy. Conclusions: An online educational intervention was associated with significant improvement in knowledge levels of rheumatologists in several important aspects of RA management, including interpretation of data from patient registries and adverse effect profiles of approved therapies. Future directions for education include additional reinforcement regarding the roles for PROs in patient management, and assessing the impact of improved rheumatologists' knowledge on care delivery and patient outcomes. References: van Tuyl LH, Michaud K. Patient-Reported Outcomes in Rheumatoid Arthritis. Rheum Dis Clin North Am. 2016 May;42(2):219–37. Epub 2016 Mar 17. Acknowledgements: The educational intervention and outcomes measurement were funded through an independent educational grant from Bristol Myers Squibb. Disclosure of Interest: E. Jackson: None declared, E. McCardell: None declared, J. Curtis Shareholder of: CORRONA; Amgen Inc.; AbbVie Inc.; Pfizer Inc; Bristol-Myers Squibb Company; Crescendo Biologics, Grant/research support from: Roche; Genentech, Inc.; UCB Pharma, Inc.; Janssen Pharmaceuticals, Inc., Consultant for: Roche; Genentech, Inc.; UCB Pharma, Inc.; Janssen Pharmaceuticals, Inc., Speakers bureau: CORRONA; Amgen Inc.; AbbVie Inc.; Pfizer Inc; Bristol-Myers Squibb Company; Crescendo Biologics